2001
DOI: 10.1366/0003702011953784
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Filtering Strategy for the Automated Detection of Ethanol by Passive Fourier Transform Infrared Spectrometry

Abstract: Digital filtering methods are evaluated for use in the automated detection of ethanol from passive Fourier transform infrared (FT-IR) data collected during laboratory and open-air remote sensing experiments. In applications in which analyte signals are overwhelmed by the overlapping signals of an interference, the use of multiple digital filters is observed to improve the sensitivity of the analyte detection. The detection strategy is based on the application of bandpass digital filters to short segments of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The methodology employed in this work was based on the application of signal processing and pattern recognition techniques directly to short segments of the interferogram data collected by the spectrometer. We have demonstrated this approach previously with data from heated plumes. , This work extends the methodology by evaluating the robustness of the algorithm to the presence of chemical species not included in the development of the classifier.…”
Section: Resultsmentioning
confidence: 99%
“…The methodology employed in this work was based on the application of signal processing and pattern recognition techniques directly to short segments of the interferogram data collected by the spectrometer. We have demonstrated this approach previously with data from heated plumes. , This work extends the methodology by evaluating the robustness of the algorithm to the presence of chemical species not included in the development of the classifier.…”
Section: Resultsmentioning
confidence: 99%
“…In a series of studies, our laboratory has demonstrated that using short segments of digitally ltered interferograms in the analysis can help to overcome these technical dif culties. [5][6][7][8][9][10] The interferogram representation of broad background spectral features decays much faster than the corresponding representation of a narrower analyte feature, thereby allowing extraction of analyte information by selecting an appropriate interferogram segment. Furtherm ore, the use of short interferogram seg-ments restricts the mirror movement of the interferometer to a shorter range, m aking faster interferogram collection possible.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore ethanol detection and discrimination requires a significantly different interferogram segment selection and digital filter implementation to attenuate unwanted background spectral features. 16 The aircraft mounted FT-IR sensor observed a wide-range of ethanol concentration profiles for over flights of the vapor generator site. The resultant analysis demonstrates both absorption and emission ethanol signatures against a variety of backgrounds.…”
Section: Ethanol Detectionmentioning
confidence: 99%